Photomath and ChatGPT-4o Applications in Fraction Learning: A Review from the Perspective of Mathematics Education Students - Mustapa, Zulfahmi; Masaniku, Rizal (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study intends to compare the use of two artificial intelligence-based applications, namely Photomath and ChatGPT-4o, in supporting fraction learning for mathematics education students. This study uses a qualitative approach with a phenomenological study design. Data were obtained through in-depth interviews and observations of three active second-semester students from a private university in Gorontalo Province who have used both applications in independent learning activities. The results indicate that Photomath is effective in providing fast and automatic solutions with systematic steps, but it is less in-depth in explaining mathematical concepts and does not present alternative solutions. In contrast, ChatGPT-4o is able to provide in-depth conceptual explanations, invite users to understand the logic behind each stage of the solution, and offer various approaches to solving problems, although the interactive process is slower. These findings indicate that Photomath is more suitable for quick practice, while ChatGPT-4o is ideal for conceptual learning and interactive discussions. This study has implications for the use of AI technology in mathematics learning and serves as a foundation for the development of more adaptive and effective digital-based teaching strategies.